Penentuan Rute Pelayaran Kapal Tramp: Integrasi Kecepatan Optimal, Displacement Kapal, dan Pemilihan Pelabuhan Pangkal - Suroso, Muhammad; Sherin Ramadhania; Nia Sastra Permata; Achmad Samudra Dewantara; Dian Fajarika (Jurnal Serambi Engineering, 2025)
PT XYZ is a shipping company that operates in the ad hoc and short-term contract (spot charter) market. The company faces challenges in selecting the most profitable cargo offers and in managing fuel consumption in order to maximise profits and minimise operational costs. This study aims to develop a mathematical model that optimises revenue through optimal cargo selection, while simultaneously minimising operational costs, including fuel consumption for the main and auxiliary engines. The model is based on the actual conditions of the company's fleet and focuses on tramp general cargo services operating under less-than-shipload (LTS) conditions. In addition to addressing fuel management, the study covers fleet routing, vessel allocation and port docking considerations. The proposed model uses a mixed integer nonlinear programming (MINLP) approach to optimise variables such as sailing speed, ship displacement and the sequence of port visits. Feasibility analysis using real fleet data and hypothetical cargo offers indicates that the model consistently produces viable solutions. Sensitivity analysis of key parameters within a variation range of -50% to +50% from their nominal values confirms that the model's outputs remain within acceptable bounds.